STRUCTURED RADIOLOGY REPORTS - V. E. Sinitsyn; M. A. Komarova; E. A. Mershina (Вестник рентгенологии и радиологии)
The paper reviews the problem of using structured radiology reports. Their salient features are as follows: to work out a protocol in accordance with some pattern, to divide it into subheadings arranged consecutively and logically and broken down by main anatomical structures, types of disease, and study, and to use standardized terminology. The RSNA proposed RadLex system is the most known example of structured reports. The experience in using these protocols has shown that the latter may improve the clearness and informative value of roentgenologists’ opinions and alleviate their understanding by physicians of other specialties. However, the systems of writing the structured radiology reports have a number of constraints for the time being, which interfere with their wide clinical introduction. Nonetheless, their use is substantially increasing in the years ahead.